Half Life of the Dollar - Mayer, Robert W. (The Review of Economics and Statistics, 1962)
in the determination of consumption patterns is rejected. The calculated marginal propensities to consume vary greatly for both races in different sections of the country (Table i) and this fact gives additional reason for rejecting the theory. The inference is clear that factors other than race are at work in the determination of consumption patterns. Although the data examined here do not rule race out as a factor in the determination of consumption patterns, they cast such serious reflections on the hypothesis as to make it, with all charity, useless. There are too many uncontrolled variables to warrant the conclusion that race alone is responsible for the difference in consumption patterns. It has become clear in this study that the concept of race as a factor in the statistical analyses of group economic behavior, such as in the assessment of so-called Negro-White savings and consumption patterns, has no more validity than left-handedness, eye pigmentation, or height. Before any realistic comparison is made on the amount spent on consumption by Negroes and Whites, adjustments should be made for the difference in their income expectation, age, dependents, education, location, financial reserves, and similar factors. Once these adjustments are made, differences attributed to race may find their origin in other factors. For example,